South Polar chart shewing the discoveries and track of H.M.S. Erebus and Terror during the years 1840. 1. 2. 3 with the lines of equal magnetic dip and variation and the position of South Magnetic Pole / by Captain Sir J.C. Ross R.N. F.R.S. Commander of the expedition - Ross, James Clark Sir, 1800-1862 (Hydrographic Office of the Admiralty, 1847)
Relief shown by hachures. "Published according to act of Parliament at the Hydrographic Office of the Admiralty, June 3rd, 1947." "Sold by R.B. Bate, Agent for the Admiralty Charts." This chart of the South Pole and the polar seas was produced in 1847 by Sir James Clark Ross (1800–1862), a British polar explorer and naval officer who was also one of Britain's leading authorities on terrestrial magnetism. After several voyages to the Arctic, from 1839 to 1843 Ross commanded the Royal Navy expedition to the Antarctic. He made important geographic and magnetic observations and discovered Victoria Land, McMurdo Sound, Mount Erebus, the Ross ice barrier, and other features of the continent. The map shows the track of Ross’s two ships, H.M.S. Erebus and H.M.S. Terror, and documents the measurements and observations made by the expedition. Relief is shown by hachures. Located more than 2,800 kilometers from the South geographic pole, the South magnetic pole is the point on the surface of the Earth at which the direction of the Earth's magnetic field is vertically upward. The “magnetic dip,” the angle between the horizontal plane and the Earth's magnetic field lines, is 90° at the South and North magnetic poles. The measurements of the dip recorded on the map show Ross’s attempt to locate the magnetic pole, which he approximated but never reached. WDL Grayscale 1:25,000,000